Dynamic Field Modulation of the Octahedral Framework in Metal Oxide Heterostructures. Issue 52 (29th October 2018) - Liu, Huajun; Dong, Yongqi; Xu, Dongwei; Karapetrova, Evguenia; Lee, Sungsik; Stan, Liliana; Zapol, Peter; Zhou, Hua; Fong, Dillon D.
Abstract: Control over the oxygen octahedral framework is widely recognized as key to the design of functional properties in perovskite oxide heterostructures. Although the oxygen octahedral framework can be manipulated during synthesis, the as‐grown oxygen octahedra generally remain fixed, preventing the development of adaptive behavior in electronic and ionotronic systems. Here, it is demonstrated that the oxygen octahedral framework can be dynamically and reversibly manipulated by an electric field through the coupling with oxygen vacancies. Studying model WO3 heterostructures during ionic liquid gating with a combination of in situ X‐ray scattering and spectroscopy, it is shown that large changes in electronic properties can arise due to the increased flexibility of the octahedral network at high vacancy concentrations. The results describe a generic framework for the construction of dynamic systems and devices with an array of field‐tunable properties. Abstract : The oxygen octahedral framework in the perovskite structure is dynamically and reversibly manipulated by an electric field through coupling with oxygen vacancies. Using ionic liquid gating in model WO3 heterostructures, in situ X‐ray scattering and spectroscopy show an increased flexibility of the octahedral network at high vacancy concentrations, giving rise to large changes in electronic properties.